Short-term and long-term outcomes of indocyanine green for sentinel lymph node biopsy in early-stage breast cancer - Bin Hua; Yao Li; Xin Yang; Xiaotian Ren; Xu Lu (World Journal of Surgical Oncology, 2022)
Abstract Background Indocyanine green (ICG) is becoming a frequently used sentinel lymph node (SLN) tracer of breast cancer in China. However, there is still a lack of data on its safety. We reported the clinical outcome of ICG as a tracer of SLN over a median 67-month follow-up period to evaluate its feasibility in clinically node-negative patients with breast cancer. Methods A total of 194 consecutive patients underwent sentinel lymph node biopsy (SLNB) with ICG, radioisotopes (RI) and methylene blue (MB), or with ICG and MB. The SLN mapping data by each tracer was recorded, and safety outcomes were analyzed through follow-up. Results With the triad mapping (N = 44), the identification rate of SLN by ICG was 95.5%, slightly higher than that of MB (86.4%) and comparable with RI (95.5%) and combined methods (95.5%, 100%) (p = 0.068). Analysis of all candidates (N = 194) demonstrated that the identification rate of SLN by ICG or by ICG and MB was 99%, significantly higher than that by MB (92.8%) (p < 0.0001). No tracer-related allergic reaction and permanent skin staining of ICG were observed. Local disease progression was reported in 2 of the 194 patients at the ipsilateral axilla. After remedial axillary lymph node dissection, no disease progression was detected at follow-up. Conclusions ICG as an SLN tracer is more accurate than MB and comparable to the combined methods and has good clinical safety. ICG can be considered a useful supplement or suitable alternative to traditional tracers.